Covalently linked molecule–electrode contacts toward robust molecular-electronics circuits - Peiris, Malwattage Chandramalika Rukmali (Curtin University, 2020)
The use of molecules as active components in electronic devices is a trend in current electronics and a potential alternative to the semiconductor-based nanoelectronics. This thesis provides a step forward in terms of potential chemistries for molecular electronics on silicon. Different molecule-electrode contacts were investigated at the macro and nano-scale using electrochemical techniques and single-molecule circuits. The work also explored the potential of silicon oxide layers as alternative materials in molecular electronics, as both a static and dynamic material.